2017
DOI: 10.1080/16546628.2017.1308118
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary fibers with high water-binding capacity and swelling capacity on gastrointestinal functions, food intake and body weight in male rats

Abstract: Objective: The aim of this study was to investigate the effects of supplementation of dietary soluble fibers with high water-binding capacity (WBC) and swelling capacity (SC) on gastrointestinal tract mass, physicochemical properties of digesta, gastrointestinal mean retention time (MRT), body weight, and food intake in male rats. Methods: Thirty-two male Sprague-Dawley rats were randomized to four equal groups and fed the control diet or diet containing 2% konjac flour (KF), pregelatinized waxy maize starch p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 45 publications
3
16
0
Order By: Relevance
“…The physiological responses to viscous and fermented dietary fibers eventually promote and prolong satiety. In a previous study, we found that supplementing rat feed with 2% CSF reduced food intake by promoting satiety [30,31]. In the present study as well, CSF significantly promoted satiety and increased weight loss when HFD was replaced with the normal feed.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The physiological responses to viscous and fermented dietary fibers eventually promote and prolong satiety. In a previous study, we found that supplementing rat feed with 2% CSF reduced food intake by promoting satiety [30,31]. In the present study as well, CSF significantly promoted satiety and increased weight loss when HFD was replaced with the normal feed.…”
Section: Discussionsupporting
confidence: 80%
“…Studies show that the mixture of hydrophilic colloid and pre-gelatinized starch can synergistically improve viscosity, water binding capacity, and stability [28,29]. In our previous works, combining guar gum, a strongly hydrophilic straight-chain β-1-4-mannose, with pre-gelatinized waxy maize starch resulted in a combined soluble fiber (CSF) with physicochemical properties similar to that of konjac flour [30,31]. In the present study, we determined the effects of this CSF on HFD-fed obese mice, and explored the relationship between dietary CSF consumption, intestinal microbiota, and metabolic status.…”
Section: Introductionmentioning
confidence: 99%
“…2016; Tan et al . 2017); here, we also found that CF lowered the ADFI of pregnant rats. Indeed, to some extent, CF could play a probiotic role in the gut as a soluble dietary fibre.…”
Section: Discussionsupporting
confidence: 79%
“…For example, acetate has been shown to be an antiinflammatory metabolite to maintain gut homeostasis, and butyrate is beneficial for modulating intestinal permeability (18,19). Our previous results showed that the combined soluble fiber materials (pregelatinized waxy maize starch plus guar gum) had a high water-binding capacity and swelling capacity (20). Pregelatinized waxy maize starch, a fermentation-resistant starch composed mainly of highly branched amorphous amylopectin, has many specific food attributes (21).…”
mentioning
confidence: 99%